Discipline And Punish? - Mistrík, Miloš (Communication Today, 2025)
Regulatory authorities in the whole Europe are moving within the limits of administrative law, so they have to ask the question about the objective of their work and the functions fulfilled by the sanctions. We are analyzing the most important ones. One of the most important functions of media regulation is a prophylactic one. The second very important is if something appears in the broadcasting stream more or less only for a short period of time, but it does not mean that it cannot have devastating impact on civil, political and sexual ethics. That because they have the function to name this case. The naming function may be meaningful not only for the audience, but also for those preparing the program and it could lead to a prophylactic function. The naming function is also linked to the function to orientate the audience in the value system. The statements made by the regulatory authority may in this way reach the education. For media education it is in fact critical to get people oriented in the world of media, and to teach them to stay detached, not to damage their own and social values. Last but not least we often see people turning to the regulatory authority with their complaints that are not specified in any way, they do not show any interest in a response, they simply need to moan at the right place. Organizations, management, or political entities also use this ventilation function sometimes. So, the ventilation function acts as a safety valve. Nobody expects broadcasters to behave voluntarily and without exceptions in a way that no sanctions would need to be applied to their programs. It is expected that it would happen, but the broadcasters would select authorities from among themselves for the correction, which would supervise compliance with the jointly selected principles. It seems to be less reliable to create regulation from the “bottom”. This system is really attractive, but it also has its own and not negligible risks. There would also be someone responsible for “discipline and punishment” from the “top”. It is mainly for this reason that the regulation authorities are here.